The Juridical Review of Making a Marriage Agreement Deed Based on a Decision of the Jepara District Court - Rahmawati, Dewi (Jurnal Konstatering, 2022)
The implication of the Constitutional Court Decision Number 69/PUU-XIII/2015 on the making of a marriage agreement deed after marriage made before a Notary changes the legal mechanism for making a marriage agreement. On a scientific basis, writing is motivated to carry out a scientific study in the form of systematic and fundamental research with the title "Juridical Review of Making a Marriage Agreement Deed Based on a Jepara District Court Decision (Case Study of Decision No.46/Pdt.P/2020/Pn.Jpa)". The research method used is a Normative juridical approach, namely legal research that uses primary data as initial data, which is then followed by secondary data or field data, in the form of interviews with District Court Judges to find relationships (correlation) between various symptoms or variables as a data collection tool. consisting of document studies, observations (observations), and interviews (interviews). Researching the Juridical Review of Making Marriage Agreement Deeds Based on Jepara District Court Decisions. In Article 1338 of the Civil Code, besides that it is also based on universally applicable provisions that the District Court is prohibited from rejecting any application and/or case that is submitted and Legal Certainty Regarding the Making of the Deed of Marriage Agreement Based on the Decision of the Jepara District Court, namely the legal consequences that arise from making a marriage agreement after marriage, namely: against the party who made it, where the marriage agreement is legally binding for the husband and wife who make it comply with the agreement contained in the marriage agreement; with regard to marital assets, each husband and wife will become stronger legally, both regarding the separation of assets and debts incurred after the marriage agreement.Keywords: Agreement; Deed; Determination; Marriage.